Den egensinnige från Kittelfjäll : En biografisk studie om utförsåkaren Bengt-Erik Grahn - Lidström, Isak (Scandia : Tidskrift för historisk forskning, 2021)
The Singular Slalom Skier from Kittelfjäll: A Biographical Study About Bengt-Erik Grahn This article is a sports biography of Bengt-Erik Grahn, a prominent figure in Swedish alpine skiing during the 1960s. By discussing representations of Bengt-Erik Grahn in the Swedish daily press and comparing these with his own life story and memories from his time as an elite alpine skier, the objective is to study the cultural identities that appear in relation to his sports career. Bengt-Erik Grahn grew up in a Sami family in Kittelfjall in the Swedish province of Vasterbotten and spent his early school years at the Sami nomad school in Tarnaby. Due to his Sami background and position as a representative of the Swedish national alpine team, the article focuses in particular on how identity constructs such as "Swedishness" and "Saminess" appear in the source material. For instance, it is argued that his Sami identity served an important function when Bengt-Erik Grahn was depicted as a Swedish sports hero. In addition, his Sami background, meager way of life, odd sporting outfit (a hand-knitted wool sweater and hat) and profession as a forestry worker were all characteristics presented in the press coverage as distinguishing the Swedish sporting identity of amateurism from what was perceived as a jet-set and playboy mentality represented by the professional Continental European alpine skiers. However, simultaneously with this idealization, Bengt-Erik Grahn's Simi heritage was also used as a stereotype to explain his aggressive and risky tactics, which often resulted in crashes in the most important competitions. Bengt-Erik Grahn's own life story in several ways offers nuance to the perceptions of the daily press. In particular, it reveals the challenges facing Bengt-Erik Grahn in his youth as he chose to focus on a career in alpine skiing. For example, there were strong expectations that a Sami skier should devote him- or herself to cross-country skiing, which was considered a traditional Sami sport at the time. Alpine ...